The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1037/per0000412
|View full text |Cite
|
Sign up to set email alerts
|

Negativity on two sides: Individuals with borderline personality disorder form negative first impressions of others and are perceived negatively by them.

Abstract: Impression formation is vital for social interactions and theorized to be negatively biased in borderline personality disorder (BPD). We assessed 2 sides of impression formation in BPD: BPD individuals as raters who form first impressions and as targets of others’ first impressions. We further investigated BPD-Rater × Target interactions. We showed videos of 52 targets (26 BPD, 26 healthy controls [HC], 46% male) to unmedicated women with BPD (n = 32), a clinical control group with social anxiety disorder (SAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 58 publications
(122 reference statements)
3
12
0
Order By: Relevance
“…Moreover, the present study adds to an existing body of evidence on negative impression formation in the Thin Slices paradigm for the BPD population [ 22 24 ]. Together with the findings depicted in our companion paper [ 48 ], the present study is the first application of the Thin Slices paradigm to a SAD sample, demonstrating that SAD individuals show a stronger tendency to ascribe negative attributes to targets than HCs. While focusing on authentic, individual targets and not crowds, our findings parallel previous evidence that highly socially anxious individuals tend to evaluate videos of crowds more negatively than low socially anxious individuals [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, the present study adds to an existing body of evidence on negative impression formation in the Thin Slices paradigm for the BPD population [ 22 24 ]. Together with the findings depicted in our companion paper [ 48 ], the present study is the first application of the Thin Slices paradigm to a SAD sample, demonstrating that SAD individuals show a stronger tendency to ascribe negative attributes to targets than HCs. While focusing on authentic, individual targets and not crowds, our findings parallel previous evidence that highly socially anxious individuals tend to evaluate videos of crowds more negatively than low socially anxious individuals [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 81%
“…The current study is part of phase III, in which we investigated BPD participants as raters of Thin Slices. We previously published data on other variables that were assessed within the present rater sample [ 48 ]. The previously published data included data from an economic game, trustworthiness, approachability, and similarity ratings (none of which were mouse-tracked).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of our first hypothesis and in line with predictions derived from an adaptation of the dynamic affect model (Ebner-Priemer et al, 2015), we found that patients with BPD report substantially higher trait levels of arousal than patients with DD and HC participants. As in previous studies, the point estimate of trait arousal in patients with BPD was more than double the value in HC participants (e.g., Stiglmayr et al, 2005;Santangelo et al, 2016;Wolff et al, 2007), whereas the difference was smaller when compared with patients with DD (e.g., Hepp et al, 2020;Stiglmayr et al, 2008). Because arousal is conceptualized as a highly unpleasant affective state (Stiglmayr et al, 2001), our finding corresponds to theoretical and empirical accounts of heightened levels of negative affect in patients with BPD (see Haskings et al, 2017 for a review).…”
Section: Group Differences In Trait Arousal and Perceived Rejectionsupporting
confidence: 76%
“…In addition, results from e-diary studies suggest that exposure to rejection events increases in arousal among in-and outpatients with BPD (Stiglmayr et al, 2005), that increases in perceived rejection are followed by higher levels of intense rage in outpatients with BPD relative to healthy controls (Berenson et al, 2011), and that among outpatients with BPD more intense experiences of rejection relate to higher acute BPD symptoms in everyday live (Miskewicz et al, 2015). More so, a series of e-diaries has shown that experiences of rejection and disagreement predict feelings of hostility and sadness in outpatients with BPD (Hepp et al, 2018; also see Hepp et al, 2017;Hepp et al, 2020). One study that used daily retrospective measures linked higher BPD features and higher distress levels in undergraduates with more interpersonal conflicts in everyday live (Haliczer et al, 2020).…”
Section: Rejection As a Predictor Of Arousal In Patients With Bpdmentioning
confidence: 98%